PERAN KUALITAS PELAYANAN, NILAI RELIGIUSITAS, DAN CITRA LEMBAGA TERHADAP PREFERENSI MUZAKKI DALAM MENUNAIKAN ZIS (STUDI KASUS LAZIS WAHDAH JAKARTA) - Agus, Agusman (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2024)
Zakat, Infak, and Sedekah (ZIS) play an essential role in poverty alleviation, wealth distribution, and national development. However, the management of ZIS in Indonesia is often suboptimal due to factors such as low awareness of zakat obligations, reluctance to donate, and lack of trust in zakat institutions. This study aims to analyze the influence of service quality, religiosity, and institutional image on muzakki's interest in fulfilling ZIS at LAZIS Wahdah Jakarta. This research employs a quantitative approach through a survey involving muzakki respondents at LAZIS Wahdah Jakarta. Data analysis uses multiple linear regression to identify the impact of these factors on muzakki's interest. The findings reveal that service quality, religiosity, and the image of zakat institutions significantly influence muzakki's intention to fulfill ZIS obligations. These results highlight the importance for zakat institutions to enhance service quality, build a positive institutional image, and strengthen muzakki religiosity values to optimize ZIS management.